Analisis Pemenuhan Standar Waktu Pembersihan Kamar Hotel terhadap Kinerja Room Attendant di Grand Praba Hotel Bandar Lampung - Zulfahmi Agustiad; Sugiman Sugiman; Ichwan Prastowo (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
Room cleanliness is very important for a hotel. A common issue in hotels is room cleanliness, leading hotels to compete for employees who can clean rooms according to the standards set by the hotel, including time and results. The purpose of this research is to observe and analyze the performance of room attendants in preparing rooms. The type of research used is qualitative descriptive research. The data collection methods in this study include observation and interviews with 6 room attendants, as well as literature review and documentation. This research uses comparative analysis to compare the standard room cleaning time with the time achieved by room attendants in cleaning rooms. The average time spent by a room attendant in cleaning a room is 33.5 or 33 minutes and 5 seconds, while the standard time set by the hotel is 30 minutes. The results of this study indicate that the time achieved by room attendants in cleaning rooms does not meet the time standards set by the hotel. Room attendants must be able to manage their time so that all work can be completed on time and cleanliness standards are maintained.